Considerations on the intellectual potential creativity - Simion Certan; Ion Certan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
The functionality of the new economic system of Republic of Moldavia, based on market relations and opened to world, frequently marked by dynamism, often by uncertainty and risk, sometimes even hostility, depends, crucially, on the innovation activity. Innovation activity, formation of innovation potential is definitely influenced by motivational politics and the reward system. The article reflects on the evolution of innovative activity, formation of innovation potential, motivational system and proposes some measures that would boost the intellectual property.
Keywords: 330; education; innovation; intellect; motivation; performance; rewards; research